PELAKSANAAN JUAL BELI YARNEN (BAYAR PANEN) DI KECAMATAN CIKELET KABUPATEN GARUT DIHUBUNGKAN DENGAN UNDANG-UNDANG NO 5 TAHUN 1999 PASAL 17 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - nurdin (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2020)
The purpose of this research is focused on: How is the practice ofbuying and selling, its legal consequences and the completion of theimplementation of the buying and selling practice of yarnen (PayHarvest) in accordance with Law No. 5/1999 concerning the prohibitionof monopolistic practices and unfair business competition in CikeletDistrict, Garut Regency. This research uses a qualitative approach, witha descriptive analytic method. The focus of this research is in CikeletDistrict, Garut Regency. Technique of studying data by using interview,observation, and documentation. While the data analysis was donethrough data reduction, data display, and retrieval. The results showedthat: 1) The practice of buying and selling agricultural products betweenfarmers and middlemen is determined to determine the price to farmerswho have borrowed capital to plant these crops. And they are required tosell their harvest to middlemen at a price that is sometimes cheaper thanother buyers, so that the farmer feels a loss, because but there is anaccount owner who is obliged to sell with the middleman 2) The legalconsequence is that the sale and purchase of this thread is very, veryinfluencing the life of the people of the Cikelet District, both on socialand economic life, some are positive, namely the fulfillment of the needsof the seller by the buyer, and some are negative, namely the rerelationships between humans, which in the end can disturb security withpeace 3) The solution is through the interaction of stakeholders includingcommunity leaders, local officials, MUI and local government (PEMDA)must intervene and participate in fostering farmers and business actorsin making buying and selling properly for problems. Law Number 5 of1999 is optimally striving for healthy and fair business competition in aparticular market, for all business actors to participate in the process ofproducing goods and services to promote fair market economic growth.